Regional Accuracy of ZTE-Based Attenuation Correction in Static [18F]FDG and Dynamic [18F]PE2I Brain PET/MR - Schramm, Georg; Koole, Michel; Willekens, Stefanie M. A.; Rezaei, Ahmadreza; Van Weehaeghe, Donatienne; Delso, Gaspar; Peeters, Ronald; Mertens, Nathalie; Nuyts, Johan; Van Laere, Koen (Frontiers in Physics, 2019)
Accurate MR-based attenuation correction (MRAC) is essential for quantitative PET/MR imaging of the brain. In this study, we analyze the regional bias caused by MRAC based on Zero-Echo-Time MR images (ZTEAC) compared to CT-based AC (CTAC) static and dynamic PET imaging. In addition, the results are compared to the performance of the Atlas-based AC (AtlasAC) implemented in the GE SIGNA PET/MR software version MP24. Methods: Thirty static [ 18 F]FDG and eleven dynamic [ 18 F]PE2I acquisitions from a SIGNA PET/MR were reconstructed using ZTEAC (using a research tool, GE Healthcare), single-subject AtlasAC (the default AC in SIGNA PET/MR software version MP24) and CTAC (from a PET/CT acquisition of the same day). In the 30 static [ 18 F]FDG reconstructions, the bias caused by ZTEAC and AtlasAC in the mean uptake of 85 anatomical volumes of interest (VOIs) of the Hammers' atlas was analyzed in PMOD. For the eleven dynamic [ 18 F]PE2I reconstructions, the bias caused by ZTEAC and AtlasAC in the non displaceable binding potential BP nd in the striatum was calculated with cerebellum as the reference region and a simplified reference tissue model. Results: The regional bias caused by ZTEAC in the static [ 18 F]FDG reconstructions ranged from -8.0% to +7.7% (mean 0.1%, SD 2.0%). For AtlasAC this bias ranged from -31.6% to +16.6% (mean -0.4%, SD 4.3%). The bias caused by AtlasAC showed a clear gradient in the cranio-caudal direction (-4.2% in the cerebellum, +6.6% in the left superior frontal gyrus). The bias in the striatal BP nd for the [ 18 F]PE2I reconstructions ranged from -0.8% to +4.8% (mean 1.5%, SD 1.4%) using ZTEAC and from -0.6% to +9.4% using AtlasAC (mean 4.2%, SD 2.6%). Conclusion: ZTEAC provides excellent quantitative accuracy for static and dynamic brain PET/MR, comparable to CTAC, and is clearly superior to the default AtlasAC implemented in the SIGNA PET/MR software version MP24.